2010
DOI: 10.1148/rg.307105054
|View full text |Cite
|
Sign up to set email alerts
|

MR Imaging and US of Female Urethral and Periurethral Disease

Abstract: The spectrum of female urethral and periurethral disorders includes both benign and malignant entities. Establishing an accurate clinical diagnosis may be challenging because symptoms and physical findings frequently overlap among the various entities. Recent technologic advances in magnetic resonance (MR) imaging and ultrasonography (US) allow more detailed evaluation of urethral and periurethral abnormalities. Advances in MR imaging hardware and pulse sequences allow high-resolution, high-contrast static and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 36 publications
2
55
0
4
Order By: Relevance
“…In the evaluation of anterior vaginal wall masses, MRI is emerging as the radiologic modality of choice due to its superb soft-tissue contrast resolution, direct multiplanar imaging capability, patient comfort, and high sensitivity for detecting fluid [6][7][8]. In fact, Rufford et al [9] have reported that misdiagnosis and delayed management of anterior vaginal wall masses often occurred before the advent of high resolution MRI.…”
Section: Discussionmentioning
confidence: 99%
“…In the evaluation of anterior vaginal wall masses, MRI is emerging as the radiologic modality of choice due to its superb soft-tissue contrast resolution, direct multiplanar imaging capability, patient comfort, and high sensitivity for detecting fluid [6][7][8]. In fact, Rufford et al [9] have reported that misdiagnosis and delayed management of anterior vaginal wall masses often occurred before the advent of high resolution MRI.…”
Section: Discussionmentioning
confidence: 99%
“…Although some reports are available in the literature, most of them elaborate either on pathological [2,3] or radiological [7,8] aspects. Therefore, treatment of such patients remains a challenge.…”
Section: Discussionmentioning
confidence: 99%
“…The distinction between urethral, peri-urethral, and anterior vaginal wall lesions may be difficult because of their anatomic proximity and overlapping clinical features. Imaging techniques such as computed tomography/magnetic resonance (CT/MR) (preferably MR) are helpful in diagnosis [7,8]. Cysto-urethrogram helps in excluding the urethral origin and invasion.…”
Section: Purposementioning
confidence: 99%
“…[5] Benign aetiologies include urethral caruncles, Skene's gland abscess/cysts, mucosal prolapse, ectopic ureterocoele, urethral diverticulum, vaginal wall cysts, Gartner's duct cysts, leiomyomas and hamartomas. [6] Rarely, malig nant lesions present as periurethral masses, inclu ding adenocarcinoma, squa mous cell carcinoma, transitional cell carcinoma, histio cytoma and sarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…[6] Rarely, malig nant lesions present as periurethral masses, inclu ding adenocarcinoma, squa mous cell carcinoma, transitional cell carcinoma, histio cytoma and sarcoma. [5,6] The diagnosis of female periurethral disease is challenging for clinicians because patients present with nonspecific signs and symptoms, including pelvic pain, dyspareunia, dysuria, urinary frequency, urinary urgency, incontinence, urethral bleed ing and urinary tract infections. [7] Clinical examination can be unreliable in distinguishing among the many types of urethral or vaginal wall masses.…”
Section: Discussionmentioning
confidence: 99%